Associations of lipoprotein subclasses and oxidative stress status in pulmonary and pulmonary plus extrapulmonary sarcoidosis - Ivanisevic, Jasmina; Vekic, Jelena; Zeljkovic, Aleksandra; Stefanovic, Aleksandra; Kotur-Stevuljevic, Jelena; Spasojevic-Kalimanovska, Vesna; Spasic, Slavica; Vucinic-Mihailovic, Violeta; Videnovic-Ivanov, Jelica; Jelic-Ivanovic, Zorana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Sarcoidosis is an inflammatory disease with pulmonary and extrapulmonary manifestations. In such pathologic conditions, increased oxidative stress and rearrangement of high-density lipoprotein (HDL) and low-density lipoprotein (LDL) may occur. Objective: This study evaluated association of oxidative stress and lipoprotein subclasses in severe forms of pulmonary and pulmonary plus extrapulmonary sarcoidosis. Methods: Lipid parameters, LDL and HDL subclass distributions, high-sensitivity C-reactive protein (hsCRP), serum amyloid A (SAA), paraoxonase 1 (PON1), malondialdehyde (MDA), total-oxidant status (TOS), sulfhydryl (SH) groups, pro-oxidant anti-oxidant balance (PAB) were determined in 77 patients (53 isolated pulmonary and 24 pulmonary plus extrapulmonary) and 139 controls. Results: Both pulmonary and extrapulmonary sarcoidosis patients had significantly higher levels of triglycerides and TOS (P<0.05) and more LDL II, LDL III, LDL IVA particles (P<0.01), but lower HDL size, SH groups (P<0.001), PON1 activity and less LDL I subclasses (P<0.05) than controls. In isolated pulmonary disease, HDL-cholesterol (P<0.01) was significantly lower whereas proportions of HDL 3a and PAB were significantly higher (P<0.05) when compared with the control group. PON1 was significantly higher in pulmonary than in combined pulmonary-extrapulmonary disease (P<0.05). In pulmonary sarcoidosis, TOS and PON1 correlated significantly with small-sized HDL particles (P<0.05). Conclusions: Both patient groups were characterized by adverse lipoprotein profile and elevated oxidative stress. In isolated pulmonary group significant associations of oxidative stress and HDL particles distribution was demonstrated. Pulmonary sarcoidosis was associated with higher PON1 activity and rearrangement of LDL particles did not depend on disease localization.